Cryopyrin-Associated Periodic Syndromes and Treatment Options - Lidija Kareva; Stavrikj, Katarina; Kristina Mironska (Scientific foundation Spiroski, 2020)
Cryopyrin-associated periodic syndromes (CAPSs) are a growing family of autoinflammatory diseases, also known as periodic fever syndromes. There are three forms of CAPS: (1) Familial Cold autoinflammatory syndrome or familial cold urticaria, (2) Muckle-wells syndrome, and (3) neonatal-onset multisystem inflammatory disease or chronic infantile neurological cutaneous articular syndrome. Genetic mutations in the NLRP3 gene were found to be present in most patients. The foremost common findings between all the CAPS disorders are rash, fever which is sometimes present at birth or in early childhood, joint problems, and conjunctivitis. More extreme forms of CAPS include more persistent inflammation that can cause hearing loss and meningitis and can lead to mental and developmental delays. Drugs for CAPS target the source of inflammation – which is the over-production of interleukin 1ß by modified cryopyrin inflammasomes. Three drugs are used to treat CAPS: Rilonacept, canakinumab, and anakirna. With these drugs, the prognosis is greatly improved, with most patients having less frequent episodes, decreased buildup of amyloid in the body, and extended life of severe cases up to adulthood.
Keywords: Cryopyrin-associated periodic syndrome; Familial cold autoinflammatory syndrome; Muckle-Wells syndrome; Neonatal-onset multisystem inflammatory disease; Anakinra; Rilonacept; Canakinumab